Paternal nutrition and cancer programming: the influence of selenium deficiency or supplementation on the susceptibility of female offspring to chemically-induced mammary carcinogenesis - Guido, Luiza Nicolosi (2016)
Breast cancer is an important public health problem. As mammary gland development is a dynamic process that initiates in embryonic life, recent evidence show that in-utero life exposure to maternal nutritional factors can alter mammary gland development and program breast cancer risk in adult life. Even tough studies focus on maternal nutrition, recent evidence show that paternal nutritional factors in-utero and during preconception also affects their female offspring mammary gland development and breast cancer susceptibility in adult life. Studies highlight epigenetic modulation of gene expression in the mammary gland as possible breast cancer programming underlying mechanisms. Selenium is a micronutrient with essential role in central aspects of embryogenesis, male fertility and that has been extensively studied as a chemopreventive agent in several breast cancer models. Among selenium possible mechanisms of action, modulation of cell proliferation, apoptosis, DNA damage, gene expression and epigenetic marks are highlighted. Thus, a rat experiment was conducted to evaluate whether paternal selenium deficiency or supplementation during preconception could affect mammary gland development and breast cancer risk, as well as possible molecular mechanisms involved. Four-week old male Sprague-Dawley rats were exposed to experimental diets (AIN93G) containing 0.15 (control), 0.05 (deficient) and 1ppm (supplemented) of selenium as sodium selenate for 9 weeks and mated with control females. At 7-week old, mammary carcinogenesis was induced in their female offspring by oral administration of 7,12 dymethylbenz[a] anthracene and mammary neoplasia development was evaluated. Paternal selenium deficiency during preconception altered mammary gland development as increased terminal end buds (TEBs) number, epithelial elongation and cell proliferation and decreased apoptosis that were associated with increased breast cancer risk (higher incidence and grade tumors). In addition, paternal selenium deficiency during preconception induced molecular alterations in the mammary gland of the female offspring such as global DNA hypomethylation, increased global levels of H3K27me3 and altered expression of genes related to early life and mammary gland development, apoptosis, cell cycle control, and DNA damage repair. Paternal selenium supplementation during preconception on the other hand did not influence breast cancer programing. Our data show that breast cancer risk can be determined in early-life stages trough the male germline molecular modulation and preconception as an important window of opportunity to start breast cancer prevention strategies. Assuring and adequate selenium intake by men could be a possible starting point.